Distribution of Polycyclic Aromatic Hydrocarbons in Water and Sediments in the Euphrates River, Iraq - Hassan, Fikrat M.; Alobaidy, Abdul Hameed M. Jawad; Salman, Jasim M.; Abdulameer, Sara H. (Iraqi Journal of Science, 2019)
The monitoring of lotic ecosystems is important for environmental health after war crisis. This study aimed to detect the fate of the sixteen polycyclic aromatic hydrocarbon compounds (PAHs) as priority pollutants in the water and sediment of Al-Hussainya River in Karbala Province. The results indicated that the concentrations in water samples ranged from 0.24–58.72 ηg.L-1 for each of the benzo(a) pyrene and benzo(g, h, i)perylene. The concentrations in sediment samples have been observed to be in a range of 0.36–119.06 μg.g-1 for naphthalene and benzo(g,h,i)perylene. Benzo(g,h,i)perylene recorded the highest concentrations in each of water and sediment samples as compared with the other compounds. The ratios of the specific PAH compounds were calculated to evaluate the possible sources of PAH contamination. These ratios reflected pyrogenic and petrogenic origins in both water and sediments.